ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL MATERI TRANSFORMASI DI KELAS XI MIPA SMAN 1 KECAMATAN KAPUR IX - Wasilah Wasilah; Iltavia Iltavia; Meli Amelia (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This research was conducted with the aim of knowing students' difficulties by looking at student mistakes in answering questions and writing literacy according to their own understanding abilities, then analyzing what factors caused students to make mistakes in solving transformation material questions. The research method used is descriptive research using a qualitative approach. The subjects of this study were 31 students of class XI MIPA 2 at SMA Negeri 1 Kapur IX District who had studied transformation material including Translation, Reflection, Rotation and Dilation. From the results of the tests given, the most frequent errors were 23% or only 7 students who answered correctly in the dilation submaterial. The fewest errors occurred in the translation submaterial, namely 35% or as many as 11 students who answered correctly. Overall, the errors of class XI MIPA 2 students are dominant in the form of errors in using formulas so that many formulas are used backwards and forwards and they are not proficient in multiplying in matrix form which is caused by an inactive or only teacher-centered learning method, and also a lack of effort. done in working on the questions given, not careful and in a hurry in solving the questions given.